Test and Numerical Analysis on Damaged Steel Beam Strengthened with Prestressed CFRP Sheet. (8th September 2021) - Hou, Wenyu; Wang, Fengchi; Wang, Lianguang
Abstract : This paper presents the experimental and numerical analysis of damaged steel beams strengthened with prestressed CFRP sheet or only strengthened with CFRP sheet. The test results showed that damaged level had a significant effect on the stiffness, yield load, and ultimate bearing capacity. And using prestressing CFRP sheet to strengthen damaged steel beam could increase the ultimate bearing capacity. The numerical analysis results showed that the damaged level had a significant effect on the stiffness and ultimate bearing capacity. The strengthened steel beam with the damaged level could exceed the steel beam without damage by about 10% in the ultimate bearing capacity. The ultimate bearing capacity would increase about 8% when the flange or web thickness increased per 1 mm. The ultimate bearing capacity would increase about 3% when the thickness or width of CFRP sheet increased per 0.05 mm or 10 mm. The bearing capacity would increase about 1.5% when the prestressed degree increased about 7%.